MiR‐424‐5p reduces ribosomal RNA and protein synthesis in muscle wasting. Issue 2 (7th December 2017) - Connolly, Martin; Paul, Richard; Farre‐Garros, Roser; Natanek, Samantha A.; Bloch, Susannah; Lee, Jen; Lorenzo, Jose P.; Patel, Harnish; Cooper, Cyrus; Sayer, Avan A.; Wort, Stephen J.; Griffiths, Mark; et al.
Abstract: Background: A loss of muscle mass occurs as a consequence of a range of chronic and acute diseases as well as in older age. This wasting results from an imbalance of protein synthesis and degradation with a reduction in synthesis and resistance to anabolic stimulation often reported features. Ribosomes are required for protein synthesis, so changes in the control of ribosome synthesis are potential contributors to muscle wasting. MicroRNAs (miRNAs) are known regulators of muscle phenotype and have been shown to modulate components of the protein synthetic pathway. One miRNA that is predicted to target a number of components of protein synthetic pathway is miR‐424‐5p, which is elevated in the quadriceps of patients with chronic obstructive pulmonary disease (COPD). Methods: Targets of miR‐424‐5p were identified by Argonaute2 pull down, and the effects of the miRNA on RNA and protein expression were determined by quantitative polymerase chain reaction and western blotting in muscle cells in vitro . Protein synthesis was determined by puromycin incorporation in vitro . The miRNA was over‐expressed in the tibialis anterior muscle of mice by electroporation and the effects quantified. Finally, quadriceps expression of the miRNA was determined by quantitative polymerase chain reaction in patients with COPD and intensive care unit (ICU)‐acquired weakness and in patients undergoing aortic surgery as well as in individuals from the Hertfordshire Sarcopenia Study. Results: Pull‐down assays showed that miR‐424‐5p bound to messenger RNAs encoding proteins associated with muscle protein synthesis. The most highly enriched messenger RNAs encoded proteins required for the Pol I RNA pre‐initiation complex required for ribosomal RNA (rRNA) transcription, (PolR1A and upstream binding transcription factor). In vitro, miR‐424‐5p reduced the expression of these RNAs, reduced rRNA levels, and inhibited protein synthesis. In mice, over‐expression of miR‐322 (rodent miR‐424 orthologue) caused fibre atrophy and reduced upstream binding transcription factor expression and rRNA levels. In humans, elevated miR‐424‐5p associated with markers of disease severity in COPD (FEV1 %), in patients undergoing aortic surgery (LVEF%), and in patients with ICU‐acquired weakness (days in ICU). In patients undergoing aortic surgery, preoperative miR‐424‐5p expression in skeletal muscle was associated with muscle loss over the following 7 days. Conclusions: These data suggest that miR‐424‐5p regulates rRNA synthesis by inhibiting Pol I pre‐initiation complex formation. Increased miR‐424‐5p expression in patients with conditions associated with muscle wasting is likely to contribute to the inhibition of protein synthesis and loss of muscle mass.